Determining of β-lactamase activity and resistanee against some antibiotics of staphyloeoeeus strains isolated from bovine mastilis - Durmuş Ali Sevinti; Mitat Şahin (Eurasian Journal of Veterinary Sciences)
This study was carried out in 256 cows which were in lactation period in Sarıkamış town of Kars. The animals were examined c1inically in the point of mastitis and inflamational changes of udders were determined with California Mastitis Test (CMT). Consequently, mastitis were diagnosed in 61 of 256 cows (23.8%). 79 milk sample were taken from 61 cows which were positive in CMT test. As a result of microbiological examination, while agent was isolated in 67 of all samples (84.8%), no bacterial agent was not isolated in 12 samples (15.2%). While Staphylococcus aureus was the most determined bacterium with the percentage of 34.3%, coagulase negative staphylococcus (KNS) followed that whit the persentage of 28.3%. Except these two groups of microorganism, Escherichia coliwas isolated in the 5.9% and Streptococcus spp. were isolated in the 16.4% of the samples. In 14 (33.3%) S. Aureus and 4 ( 9.5%) KNS strains, of all isolated staphylococcus strains, β -lacternase was found positive. In the study the resi stance of staphylococcus strains against antibiotics were determined as follows; 59.5% penicillin, 38.1% amoxicillin, 7.1% amoxicillin-c1avulonic acid, 4.8% c1oxacillin, 11.9% enrofloxacin and all strains were found sensitiye against vancomicin. The β -lactarnase activity of the strains was determined to have an important role in resistance against β -lactarn group antibiotics.